Draft Genome Sequence of Lachancea lanzarotensis CBS 12615(T), an Ascomycetous Yeast Isolated from Grapes - Sarilar, Véronique (Genome Announc, 2015)
We report the genome sequencing of the yeast Lachancea lanzarotensis CBS 12615(T). The assembly comprises 24 scaffolds, for a total size of 11.46 Mbp. The annotation revealed 5,058 putative protein-coding genes. Detection of seven centromeres supports a chromosome fusion, which occurred after divergence from Lachancea thermotolerans and Lachancea kluyveri.